The Problem of Justifying Personal and National Guilt for the Crimes of the Nazi Regime in the Light of Melita Maschmann’s "Bilans" and Alfons Heck’s "Hitler’s Child" - Szułczyński, Piotr (Sensus Historiae, 2025)
The article is an attempt to comparatively analyze the memories of two former Hitler Youth activists - Alfons Heck and Melita Maschmann in relation to the issue of personal and national guilt for the crimes of the Nazi regime. The author examines how the multi-stage indoctrination to which the youth in the Third Reich was subjected led to complete devotion to Adolf Hitler and acceptance of the principles of National Socialist ideology. The review compares different ways of justifying guilt: from unwavering faith in Goebbels’ propaganda, through attempts to deny facts during Allied interrogations, to a clash with the brutal truth about Nazi responsibility for the Holocaust. The analysis highlights the authors’ different attitudes toward their own past: Heck’s relatively quick acceptance of it, marked by sincere remorse, and Maschmann's suppression of remorse, explaining it as “innocent suffering.” The text emphasizes the tragedy of the situation of German youth, who, after the fall of the Nazi system, had to find themselves in a new reality and live with the burden of responsibility for Nazi crimes.